1972
DOI: 10.1136/bmj.4.5840.610
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocystic disease of pancreas and Crohn's disease.

Abstract: place much reliance on om tie infection rates from difet hospitals because of differences in methods of treatment and in prevalent strains of bacieria. Thes are by no means the only variables. We have been studying wound infections at this hospit for the past two years and have ied out ontinuous monitorig of all infections for over a year. An initial difficulty was to define what constitutes a wound infection. When a wound discare

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The combination of CF and Crohn's disease has been reported previously [1][2][3][4][5][6][7][8][9][10]. However, the uniqueness of this case is the fact that the presenting feature of Crohn's disease was masked as abdominal wall cellulitis localized at the right lumbar region.…”
Section: Discussionmentioning
confidence: 56%
“…The combination of CF and Crohn's disease has been reported previously [1][2][3][4][5][6][7][8][9][10]. However, the uniqueness of this case is the fact that the presenting feature of Crohn's disease was masked as abdominal wall cellulitis localized at the right lumbar region.…”
Section: Discussionmentioning
confidence: 56%
“…The concurrence of CF and CD was first reported in a 7-y-old girl in 1972 [1]. Since that time, additional cases reports have emerged, followed by individual reports and small case series from Germany, the United States, Israel, the United Kingdom, and Australia [2,411].…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis (CF) and Crohn's disease (CD) were first described in the same patient in 1972 [1]. Subsequent reports and a national survey in the United States revealed that the incidence of CD in patients with CF is significantly increased over that of the general population [2] Giant inflammatory polyposis (GIP) is a rare manifestation of idiopathic inflammatory bowel disease (IBD).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, three publications have dealt with the simultaneous occurrence of CF and CD (10-12). In the girl described by O'Connor and Lawson (10), CF was diagnosed by the age of I year. Rectal bleeding, diarrhea, and an anal fistula resistant to therapy were the presenting symptoms of CD by the age of9 years .…”
Section: Discussionmentioning
confidence: 99%